2015
DOI: 10.3892/ijo.2015.2888
|View full text |Cite
|
Sign up to set email alerts
|

The anthraquinone derivative Emodin inhibits angiogenesis and metastasis through downregulating Runx2 activity in breast cancer

Abstract: Emodin (EMD) is an anthraquinone derivative extracted from the root and rhizome of Rheum palmatum L. which exhibits a range of activities, including anti-bacterial, antitumor, diuretic and vasorelaxant effects. The ability to inhibit metastasis and angiogenesis was shown in previous pharmacological studies, but clear information to address EMD affecting angiogenesis and metastasis in human breast cancer is still lacking. In the present study, we evaluated a possible role for EMD in angiogenesis and metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The tumor inhibition rates were higher in the latter two groups than that in low-dose emodin group. It was also revealed that emodin attenuated tumor cell-induced metastasis and angiogenesis, both in vitro and in vivo [ 205 ]. Finally, emodin has been reported to inhibit the growth of pancreatic cancer PANC-1 cells, which may be related to the demethylation of tumor suppressor genes.…”
Section: In Vitro Biological Activities Of Natumentioning
confidence: 99%
“…The tumor inhibition rates were higher in the latter two groups than that in low-dose emodin group. It was also revealed that emodin attenuated tumor cell-induced metastasis and angiogenesis, both in vitro and in vivo [ 205 ]. Finally, emodin has been reported to inhibit the growth of pancreatic cancer PANC-1 cells, which may be related to the demethylation of tumor suppressor genes.…”
Section: In Vitro Biological Activities Of Natumentioning
confidence: 99%
“…CD34 antibody is a credible marker for MVD evaluation. Recent studies have found associations between MVD and poor disease course in breast, lung, stomach, and bladder cancer [35] [36] [37].…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to Ma J et al and Guan YY et al showed the anthraquinone derivative emodin and Raddeanin A downregulating VEGFR2 activity in breast cancer and colorectal tumor rat model in vivo. 71,72 Molecular docking based virtual screenings using a protein target with experimentally determined structures are in lead discovery for various drug developments. 73 Molecular dynamic simulation is a standard tool for understanding physical interaction between a receptor and ligand (small molecule) in drug discovery.…”
Section: Discussionmentioning
confidence: 99%